Chemical profiling, antibacterial and antiparasitic studies of Imperata cylindrica - P.B. Lalthanpuii, Zarzokimi, Kholhring Lalchhandama (Journal of Applied Pharmaceutical Science, 2019)
Imperata cylindrica is a common grass with little known medicinal properties. The underground part (comprising rhizome with roots) is used by the Mizo people for the treatment of microbial and intestinal worm infections. To understand the chemical and pharmacological properties of the plant part, a methanol extract was prepared in a Soxhlet apparatus, and the extract was concentrated using a vacuum rotary evaporator. Chemical analysis was done using gas chromatography-mass spectrometry. Antibacterial activity was tested by Kirby–Bauer test and antiparasitic activity by survival test in vitro. Fourteen volatile compounds were detected; out of which the most abundant were n-hexadecanoic acid and (Z)-18-octadec-9-enolide. Some compounds detected including 2-methoxy-4-vinylphenol, 6-methylenebicyclo [3.2.0] hept-3-en-2-one and phenol,2,4-bis (1,1-dimethylethyl) are already known biologically active compounds. The plant extract was effective against all bacteria tested that included Gram-negative bacteria such as Pseudomonas aeruginosa and Klebsiella pneumoniae, and a Gram-positive bacterium Bacillus subtilis. It was also effective against two avian intestinal worms such as the tapeworm Raillietina echinobothrida and the roundworm Ascaridia galli. These findings reveal the importance of this plant as a source of therapeutic compounds.
Keywords: Antibacterial activity, antiparasitic activity, GC-MS, Imperata cylindrica, nematode, tapeworm.